2012
DOI: 10.1146/annurev-publhealth-031811-124603
|View full text |Cite
|
Sign up to set email alerts
|

How Society Shapes the Health Gradient: Work-Related Health Inequalities in a Comparative Perspective

Abstract: Analyses in comparative political economy have the potential to contribute to understanding health inequalities within and between societies. This article uses a varieties of capitalism approach that groups high-income countries into coordinated market economies (CME) and liberal market economies (LME) with different labor market institutions and degrees of employment and unemployment protection that may give rise to or mediate work-related health inequalities. We illustrate this approach by presenting two lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 81 publications
4
61
0
Order By: Relevance
“…Labor market experiences related to the availability and nature of work are embedded within a labor market and social context (7). Four contextual levels are defined: workplace/organizational, labor market, societal, and supranational (see table 2).…”
Section: Labor Market and Social Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…Labor market experiences related to the availability and nature of work are embedded within a labor market and social context (7). Four contextual levels are defined: workplace/organizational, labor market, societal, and supranational (see table 2).…”
Section: Labor Market and Social Contextsmentioning
confidence: 99%
“…Transitions are significant changes in physiological, psychological, social or material states (7,21). Transitions (ie, health status, life course and labor market transi tions) have the potential for short and longterm health and labor market outcomes.…”
Section: Amick Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez used data from the United States, Germany and Britain and found that unemployed workers receiving different types of government entitlement benefits (including unemployment benefits) reported similar health status as full-time employed workers, suggesting that such support programs can buffer the health effects of job loss (Rodriguez 2001). Other studies have reported protective effects of government entitlement benefits for depression symptoms among unemployed women (25); poor self-rated health among minimum and medium skill level jobs (21); and poor mental health among unemployed workers in Spain (26). While most of these studies find a positive association between unemployment benefits and health, a key limitation is the lack of attention to selection.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies suggest that unemployment benefits may ameliorate some of the negative health effects of job loss (19)(20)(21), prior studies have not accounted for preexisting differences between benefit recipients and nonrecipients. A potential concern is therefore that benefit recipients are a priori in comparatively better health than their non-recipient counterparts.…”
Section: Introductionmentioning
confidence: 99%